Robert B. Parker's The bitterest pill [compact disc, unabridged] - Coleman, Reed Farrel, 1956-; Parker, Robert B., 1932-2010 (Jesse Stone series, 2019)
When a popular cheerleader dies of a suspected overdose, Police Chief Stone battles school administrators, teachers, distrustful students, and overprotective parents as he tries to unravel the drug supply chain and expose the criminals behind it.